A case of an extreme white coat effect. (2nd January 2020) - Nyvad, Jakob; Reinhard, Mark; Christensen, Kent L.
Abstract: In this report, we present a challenging case of a 63-year-old Caucasian woman with an extreme stress response to blood pressure (BP) measurements. Office- and ambulatory BP measurements consistently found systolic BP above 200 mmHg. However, antihypertensive medication made her dizzy and extremely unwell, and she could barely tolerate treatment with a moderate dose of angiotensin-converting enzyme (ACE) inhibitor. Finger-cuff-based measurements (Finapres Finometer®) revealed extreme hypertension in relation to contact with medical professionals, but hypotension when the patient was seated alone unobserved. Months after, the patient suffered a hemorrhagic stroke possibly related to her extreme BP-fluctuations in stressful situations.